Investors’ Trading, Market Timing, and Implementation Shortfall: Evidence from the US Financial Market - Bhuyan, Rafiqul; Khandoker, Mohammad Sogir Hossain; Akter, Lamia; Robbani, Mohammad G. (International Journal of Accounting & Finance Review, 2020)
In this research, we evaluate the US investors’ trading pattern and choice of market timing in the presence of implementation shortfall. Results show that when investors decide to trade, implementation shortfall is being ignored. It is observed that stock performance on Wednesday is positive in the presence of positive and significant implementation shortfall i.e., traders do not seem to manage implementation shortfall during trading on Wednesday. It is also observed that investors seem to ignore the implementation shortfall in April. This behavior seems to persist in other types of market times such as turn-of-the-month, week-of-the-month, and quarter-of-the-year effects on implementation shortfall. We conclude that investors behave aggressively to buy stocks during certain days and times of the year ignoring implementation shortfall.